Analysis Of Financial Performance In Soe Sharia Commercial Banks In Indonesia Before And After The Merger With The Vecm Method (Vector Error Correction Model) - Shinta Kemala Dewi; Nurlaila Nurlaila (Sean Institute, 2022)
This study uses the VECM (Vector Error Correction Model) method to examine the financial performance of Islamic banks at three state-owned Islamic banks before and after the merger. The sample in this study used a purposive sampling technique. The samples for this study were 3 BUMN banks that were merged, namely Mandiri Syariah Bank (BSM), BNI Syariah, and BRI Syariah with a 4-year period from 2018-2021. The data analysis method used is the VECM (Vector Error Correction Model) method with eviews 9 analysis tools. There are 3 research variables namely profitability, solvency/leverage and liquidity, with the following indicators: profitability (ROA, NPM), Solvency (DER, DAR) and Liquidity (CR). Profitability (ROA, NPM), Solvency (DER, DAR), Liquidity (CR). The results of this study indicate that there are differences in the variables between the financial performance of Islamic banking before and after the merger. In addition, there is a mutually influencing relationship between variable indicators, which means that each variable indicator can influence the ups and downs of post-merger Islamic banking financial performance.